Agronomic performance of sweetcorn populations derived from croáes betweetcorn and field corn - Butron, A.=700 1 Alvarez, A.; Revilla, P.; Malvar, R.A.; Rodriguez, V.M.; Ruiz de Galarreta, J.I.; Ordas, A.
(Es, En)
Ilus., 22 ref.
Keywords: ZEA MAYS; HIBRIDACION; MAIZ DULCE; ESPAÑA; MAIZ GRANO; SPANISH JOURNAL OF AGRICULTURAL RESEARCH